Hemodynamic Shifts in Children During the Induction into Narcosis P - Talat Agzamkhodjaev1, Anvar Yusupov2, Makhfuza Ismailova3, Mamur Talipov4, Isfandiyor Mamatkulov (Institute of Medico-legal Publications Pvt Ltd, 2020)
The article focuses on the study of hemodynamics of children during the period of induction into anesthesia.The analysis of the study results has been carried out – 80 children aged 3 to 14 years undergone medicalprocedures on diseases of abdominal cavity and anorectal area. The study results have shown that thecombination of sevoflurane and ketamine in small doses has caused an effective analgesic effect with asignificant vegetative stabilizing effect providing a stable course of the following stages of anesthesia andpostanesthetic period.